Drug users hosting in a Basic Health Unit - Daniel Goulart Rigotti; Ana Paula Rigon Francischetti Garcia; Natália Galvão Silva; Thalita Mendes Mitsunaga; Vanessa Pellegrino Toledo (Universidade Federal do Ceará, 2016)
Objective : to understand the care of drug users in a Basic Health Unit. Methods : a qualitative study through semi-structured interviews with 13 subjects in a Basic Care Unit of a health district. Results : after thematic analysis, three categories were revealed: Home as routing and factors that determine the practice, showing that factors such as feelings and personal characteristics of workers, lack of training and awareness of lower resoluteness by nursing professionals held a routing logic avoided accountability for the care, keeping its fragmentation; Host, link and routing, in which bond and co-responsibility were incipient practices, hindering the comprehensive care; and Home and predominant care models, showing that the host supported on the biomedical model, but contradictions were observed between different models and practices. Conclusion : it is necessary to overcome the biomedical model, from the expanded clinic and restructuring vocational training.